Sustainability Analysis of Marine Ecotourism Based on Small Island Resources in GITANADA Island Sea, West Lombok Regency, Indonesia - Sukuryadi (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research The multidimensional sustainability index is 54.729, which falls into the moderately sustainable category. The ecological and social dimensions are relatively good, while the economic, institutional, and technological and infrastructure dimensions are less sustainable. Strategies to enhance labor absorption and create local business opportunities in supporting the development of marine ecotourism. Strengthen supporting infrastructure are priority steps in supporting the development of marine ecotourism. Abstract The sustainability of marine ecotourism in small island regions has been extensively studied through various dimensions, including ecological suitability, carrying capacity, community participation, and institutional and local economic strategies. However, most previous studies have addressed these dimensions separately and have not developed an integrative approach that encompasses all dimensions of sustainability within a comprehensive analytical framework. This study aims to analyze the sustainability of marine ecotourism based on small island resources through a multidimensional approach, as well as to identify the most influential sensitive indicators on the sustainability index value across five main dimensions: ecology, social, economic, institutional, and technology and infrastructure. The method approach used is Rapid Appraisal for Fisheries (RAPFISH), with the support of Multidimensional Scaling (MDS), Monte Carlo, leverage, and Analytical Hierarchy Process (AHP) analysis. The results of the study show that the multidimensional sustainability index is 54.821, which falls into the moderately sustainable category. The ecological and social dimensions are relatively good, while the economic, institutional, and technological and infrastructure dimensions are less sustainable. Therefore, strategies to enhance labor absorption, create local business opportunities, and strengthen supporting infrastructure are priority steps in supporting the development of marine ecotourism. As a result, it is expected to strengthen the competitiveness of the destination, expand economic benefits for local communities, and create an adaptive and sustainable marine ecotourism management system.